Advanced Parental Age at Conception and Sex Affects Mitochondrial DNA Copy Number in Human and Fruit Flies - Mengel-From, Jonas (J Gerontol A Biol Sci Med Sci, 2019)
Aging is a multifactorial trait caused by early as well as late-life circumstances. A society trend that parents deliberately delay having children is of concern to health professionals, for example as advanced parental age at conception increases disease risk profiles in offspring. We here aim to study if advanced parental age at conception affects mitochondrial DNA content, a cross-species biomarker of general health, in adult human twin offspring and in a model organism. We find no deteriorated mitochondrial DNA content at advanced parental age at conception, but human mitochondrial DNA content was higher in females than males, and the difference was twofold higher at advanced maternal age at conception. Similar parental age effects and sex-specific differences in mitochondrial DNA content were found in Drosophila melanogaster. In addition, parental longevity in humans associates with both mitochondrial DNA content and parental age at conception; thus, we carefully propose that a poorer disease risk profile from advanced parental age at conception might be surpassed by superior effects of parental successful late-life reproduction that associate with parental longevity.